The 1636 Ruthenian Translation of the Czech Lucidarius (*Olomouc, 1622): Interpolations in an Ukrainian Manuscript Copy of the Early 19th Century - Temčinas, Sergejus (Slavistica Vilnensis, 2022)
The article focuses on the textual history of the Ruthenian translation of the Czech book entitled Lucidář (Lucidarius), a medieval encyclopedic treatise consisting of the student’s questions and the teacher’s answers, which was most widespread in the Cyrillic manuscript tradition of the Polish-Lithuanian Commonwealth (the Grand Duchy of Lithuania and the Kingdom of Poland). This translation was made in 1636 from a non-extant edition (*Olomouc, 1622) and is represented by at least nine manuscript copies: five of them have been published and other four still remain practically unknown (kept at St. Petersburg and Yaroslavl). The latest manuscript copy of the early 19th century, which is of Ukrainian origin and is now kept in the collection of T. V. Kibalchich (St. Petersburg, National Library of Russia, Main Collection of the Manuscript Books (f. 550), Q.I.910, 21 f.), contains interpolations from three printed sources: Ioannikiy Galyatovsky’s Ključ razuměnija (Kyiv, 1659 or Lviv, 1663 or 1665), Cyril Tranquillion-Stavrovetsky’s Zercalo bogoslovija (Pochaiv, 1618 or Univ, 1692), andthe Chronicle by Dimitry of Rostov (Moscow, 1799–1800). These interpolations testify to the textual development of the Ruthenian translation of the Czech Lucidarius at the very end of its manuscript tradition. In the manuscript, the sources of these interpolations are explicitaly named without indicating the year and place of publication. The present article aims to establish the methods applied by an anonymous scribe to his printed sources and to identify the editions used by the compiler.
Keywords: Slavic literature; translations; reception; Lucidarius; interpolation